Writing To Speak: Integrating Oral Communication Skills Through A Tourist Brochure - Emaliana, Ive (EDUCAFL : E-Journal of Education of English as a Foreign Language, 2012)
The aim of this paper is to present an alternative technique in the teaching and learning for the higher institution of learning. This tourist brochure presents a new approach of creativity as a method of teaching and learning in the non-English departments.The whole idea is to make the studentsâ presentations interesting by using visuals. Having students write a tourist brochure as a project offers important benefits like providing students with a context, a real-world purpose for writing, and strong motivation to find the words and develop the writing skills that will serve their needs. By breaking the boundaries between traditional courses by integrating writing and speaking skills, the studentsâ communicative competence will be improved. In the activities described here, integrating writing and speaking skills deepen studentsâ understanding on how to write a tourist brochure, and most importantly, let them apply the information they have written into authentic speaking practice that improve their fluency.Keywords: a tourist brochure, writing, speaking, communicative competence